تطويع الرقابة المصرفية لبنك الجزائر لدعم النشاط المصرفي للبنوك الإسلامية العاملة في الجزائر - حمو، محمد (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2023)
هدفت هذه الدراسة إلى تبيان وظيفة الرقابة المصرفية المركزية التي تخضع لها البنوك الإسلامية والحاجة إلى تطويعها، وذلك بالتركيز على أهم أدوات الرقابة المصرفية التي تمارس على البنوك ومدى ملائمة هذه الأدوات لطبيعة النشاط المصرفي الإسلامي، كما هدفت الدراسة إلى تشخيص واقع رقابة بنك الجزائر على فروع البنوك الإسلامية أو النوافذ الإسلامية التي تعمل في الجزائر، ومدى ملائمة هذه الرقابة لطبيعة وخصوصيات عمل هذه الفروع والنوافذ المصرفية. هذا وقد خلصت ذات الدراسة إلى أن بنك الجزائر يطبق على فروع البنوك الإسلامية وكذا النوافذ ذات الأدوات التي يطبقها على البنوك التجارية، وقد لا تتلاءم هذه الأدوات مع طبيعة عمل فروع البنوك الإسلامية والنوافذ على النحو الذي يؤثر على علاقتها ببنك الجزائر من الجانب الرقابي، هذا وقد أوصت الدراسة بضرورة تعزيز الدور الرقابي لبنك الجزائر على النحو الذي ينظم النشاط المصرفي الإسلامي في الجزائر من خلال إصدار تشريعات ملائمة لطبيعة عمل فروع البنوك الإسلامية، والعمل على إنشاء هيئة عليا للرقابة الشرعية على مستوى بنك الجزائر وتدريب الموارد البشرية لتمكينهم من مهارات وأصول العمل المصرفي الإسلامي، فضلاً على ضرورة الاستفادة من تجارب العمل المصرفي الإسلامي الناجحة. The aim of this study was to clarify the function of central banking supervision to which Islamic banks are subject and the need to adapt it, by focusing on the most important banking supervision tools practiced on banks and the suitability of these tools for the nature of Islamic banking activity. The study also aimed at diagnosing the reality of Bank of Algeria's control over the branches of Islamic banks or Islamic windows operating in Algeria, and the extent to which this control is appropriate to the nature and specifics of the work of these branches and banking windows. The same study concluded that the Bank of Algeria adapts branches of Islamic banks as well as the windows with the tools which applied to commercial banks, these tools may not fit with the nature of the work of Islamic bank branches and windows,, in a way that affects their relationship with the Bank of Algeria in the regulatory side. The study recommended the need to strengthen the supervisory role of the Bank of Algeria in the manner that regulates Islamic banking activity in Algeria by issuing appropriate legislation for the nature of the work of branches of Islamic banks, working on the establishment of a supreme Sharia supervisory board at the level of the Bank of Algeria and training human resources to enable them with the skills and assets of Islamic banking In addition, it is necessary to take advantage of the successful Islamic banking experiences.
Keywords: الرقابة المصرفية -- النشاط المصرفي -- البنوك الإسلامية -- الجزائر